Allelic variations of HMW-GS and LMW-GS and quality analysis in Yannong series wheat cultivars/derivative lines - Sun, Nina; Mu, Yanjun; Wang, Dongmei; Li, Jiatong; Yuan, Tangyu; Liu, Wei; Yu, Ningning; Xu, Xiaozhe; Li, Linzhi; Jin, Yuli; Ma, Pengtao (Frontiers in Genetics, 2024)
Gluten quality is one of the most important traits of the common wheat (Triticum aestivum L.). In Chinese wheat production, Yannong series cultivars/derivative lines possess unique characteristics and play an important role in both yield and quality contribution. To dissect their genetic basis of the gluten quality, in this study, allelic variations of high-molecular-weight glutenin subunit (HMW-GS) and low-molecular-weight glutenin subunit (LMW-GS) in 30 Yannong series wheat cultivars/derivative lines and three check cultivars were evaluated using the allele-specific molecular markers, and six crucial quality indexes were also further measured and analyzed. The results demonstrated that the frequencies of HMW-GSs By8, Dx5+Dy10 and Dx5+Dy10+Dy12 in these 30 genotypes and three check cultivars accounted for 87.9%, 24.2% and 9.1%, respectively. For the allelic variations of LMW-GSs, Glu-A3a, Glu-A3b, Glu-A3c, Glu-A3f, and Glu-A3g were identified in 18, 9, 13, 11 and 2 genotypes, respectively; Glu-B3d, Glu-B3g and Glu-B3f were identified in 13, 23 and 4 genotypes, respectively. Notably, Yannong 999, containing By8+Dx5+Dy10, and Jinan 17 containing By8+Dy12 both meet the national standard for high-quality wheat and belong to the category of first-class high-quality strong gluten wheat. These findings can provide reference for wheat quality improvement and popularization in the production.